Lifelong motor development - Gabbard, Carl 1948- (Philadelphia Wolters Kluwer Health, 2018)
Approaching motor development as the study of change, Lifelong Motor Development , 7th Edition, offers the most up-to-date, comprehensive, research-based coverage of motor behavior across the life span available today. Rather than introducing a single theory, the book covers the most prominent theories and views that underscore our understanding of change in motor development to help students truly understand the multicausal and complex nature of motor development across the lifespan. Now in vibrant full color, the 7th Edition offers much that is new, including new content that reflects the latest research, new pedagogy, new illustrations, and an enhanced suite of resources that help students succeed and ensure easy integration into the classroom.
Introduction to the developmental perspective -- Heredity and neurological changes -- Physical growth changes -- Physiological changes -- Factors affecting growth and development -- Perceptual development -- Information processing and motor control -- Early movement behavior -- Motor behavior during early childhood -- Motor behavior during later childhood and adolescence -- Motor behavior in the adult years -- Atypical motor behavior -- Assessment -- Sociocultural influences on motor development.
Includes bibliographical references and index.
Keywords: Motor ability; Human growth; Human locomotion